Information design : an introduction - Pettersson, Rune, 1943- (Document design companion series ;, 2002)
The goal of communication-oriented design of messages should always be clarity of communication. In information design the task of the sender is actually not completed until the receivers have received and understood the intended messages. Information Design - An introduction includes chapters explaining verbo-visual communication, information and message design principles, design processes, and design tools. These chapters can be seen as a general framework for production of information and learning materials. Based on theories for verbo-visual communication this book presents several practial.